Analisis Kestabilan Lereng Puncak Jaya di CV. Tekad Jaya Nagari Tanjung Gadang, Kecamatan Lareh Sago Halaban, Kabupaten 50 Kota. - Jeremyes A.P; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. The mining industry is very influential industry in various aspects of life today, such as building offices, housing, and etc. The mining industry has also influenced Indonesia's economic development. CV. Tekad Jaya is a limestone mining company that has not conducted a study on slope stability in the mining area. Because there has not been a study of the stability of the slope, it makes workers who are working in the area around the slope uncomfortable. Therefore, the company wants to conduct a study on the stability analysis of puncak jaya. This study, the RMR (rock mass rating) method was used to measure the rock. For geotechnical parameters, tests were carried out with the results of the physical and mechanical properties of limestone rock with the unit weight value of 9.51 KN/m3 , the saturation weight of 11.80 KN/m3 , and in a dry state the weight value is 6.62 KN/m3 with cohesion (c) = 20.3 KN/m2 and the friction angel (ϕ) = 60.675˚. Analysis of the safety factor (FK) and slope modeling used the Janbu simplified method. The results of the first study the type of landslide that may occur in the mining area is the direct landslide with a potential of 20%. The second results of the Rock Mass Classification based on the RMR Rock Method have good quality and in class II. The third recommendations for safety factor slopes for mining areas that have a height of 80 m with a slope of 76˚ have been changed to a height of 80 m with a slope of 67˚, then the safety factor values for each are in three conditions, is: in the naturale state 1,432, saturated 1,335, and dry 1,546 Keywords: physical and mechanical properties of rocks, rock classification, RQD, slope geometry, slope stability, janbu simplefied